Analisis dan Estimasi Dampak Longsorlahan terhadap Jaringan Jalan di Kecamatan Samigaluh, Kabupaten Kulonprogo - Eko Setya Nugroho; Danang Sri Hadmoko; Cees van Westen; Nanette Kingma (Universitas Muhammadiyah Surakarta, 2012)
In this study, direct risk assessment was developed for various scenarios on the basis of hazard (e.g. spatial probability, temporal probability and magnitude class), vulnerability and estimating cost of road damage. Indirect risk assessment was derived from traffic interruption. The impact of landslide both direct and indirect impact were analyzed in the road segment 174. The research results show the highest direct impact of debris slide type of magnitude I located in the 20th mapping unit. The lowest direct impact of debris slide type of magnitude I can be founded in the 18th mapping unit. The direct impact of rock fall type of magnitude I which is located in the 6th mapping unit. Meanwhile, indirect impact which was caused by road blockage is Rp. 4,593,607.20 and Rp. 4,692,794.40 by using network analysis and community perception methods respectively. After class classification, road segment 174 is dominated by very low hazard, very low vulnerability and very low direct impact.